The Peruvian Navy as an instrument of peace in the context of the Treaty of Lima of 1929. An example of naval diplomacy - Laguerre Kleimann, Michel (2023)
The Treaty of Lima signed on June 3, 1929, put an end to the diplomatic pending that began after the war over Guano and Salitre, a war that began fifty years ago. Many of those who fought in that war and lived through the fateful years that followed, were actors and witnesses to the negotiation process that would conclude one of the most sensitive aspects of the Treaty of Ancon: the return of the captive provinces. The participation of the Peruvian Navy, both before, during and after the signing of the Treaty, meant an example of Naval Diplomacy, demonstrating its old and current participation in the Foreign Policy of the Republic of Peru.